151 A Web Application to Establish Customized Feeding Program and Nutrient Specifications for Highly Prolific Sows. (7th May 2021) - Jerez-Bogota, Kevin S; Ramirez-Camba, Christian D; Navales, Ron A; Vier, Carine M; Lu, Ning; Cast, Wayne R; Dritz, Steve S; Orlando, Uislei A
Abstract: A web application was developed to provide a dynamic feeding program for PIC maternal dam lines during gilt development, gestation, peri-partum, lactation and wean-to-service interval (WSI). These recommendations for each production phase are based on peer-reviewed large-scale commercial research. The tool was developed using the Shiny package of R and includes CSS themes, html widgets, and JavaScript actions. Inputs, include pigs weaned per sow per year (PWSY), farrowing rate (FR), total born (TB), replacement rate, the existing feeding program of the breeding herd and the diet energy and standardized ileal digestible (SID) lysine (Lys) levels. Outputs include the feeding program, nutrient specifications and estimates of economic opportunity and performance improvement. The feeding program is based on user-defined energy and SID Lys levels for the gestation and lactation diets and the PIC nutrient recommendations for the breeding herd. Correspondingly, recommended specifications of other nutrients in the diets are provided and calculated based on the recommended feeding program. The tool provides economic and productivity opportunity analysis by comparing the PIC recommendations and the current user feeding programs. Improvement in PWSY is driven by the energy intake impact on caliper score during breeding and farrowing and consequently to FR and TB. This web application can be used by nutritionists and production managers to compare their current feeding practices to PIC recommendations for highly prolific sows. This will aid in their decision-making process regarding nutrition and feeding programs considering productivity and profitability outcomes.